Error analysis of structural particle "de" by Malaysian students studying Chinese language abroad (IR) - Afiqah Sabariah Khalidar (2016)
Research on chinese word "de" is complex and old. In Teaching Chinese as A Second Language, usage of "de" word is not only important but also complicated. To foreign students, using Chinese word "de" is a very hard grammar to learn. In China, they were many research on structural particle "de", but research on error analysis of foreign students studying Chinese in structural particle "de" is still incomplete, because most of the researches are on description phase only. To this day, there is still no research has been made on error analysis of Malaysian studying abroad in Chinese language on structural particle "de". First, I made a comparison in classification and usage of structural particle word in Malay language and structural particle word "de" in Chinese language. In accordance with structural particle word in Malay language and structural particle word "de" in Chinese language, then I made a test to beginner, intermediate and advance learner of Malaysian studying abroad in Chinese language. After analyzing and making a statistic on their test, I found that they have four types of errors which are omitting of "de" error, adding of "de" error, multi-attributive position of "de" error and word order error. Multi-attributive position of "de" error is the main problem for students of every level. This happened because multi-attributive position of "de" is complex. For beginner students, multi-attributive position of "de" error is their main problem, but the adding of "de" error is also one of their most made errors. For intermediate students, their main errors are also on multi-attributive position of "de" but they also made numerous errors on the omission of "de". Advanced level students' common errors are also on multiattributive position of "de" error but their errors of omitting "de" and the adding of "de" are balanced. Based on the analysation of their errors, I have sum up the causes of those errors kept being made are because of the negative transfer of first language, overgeneralization, learning strategies interference and inadequate of learning materials. Lastly, I made suggestions to lecturers and teaching materials as to how to overcome their errors on usage of Chinese structural particle "de".